Excellent Service in The Perspective of Social Reconstruction: Public Perception and Expectation - Zamroni, Zamroni; Fajri, Muhammad (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to identify and analyze excellent service in Madrasahs based on the perspective of social reconstruction by examining public perceptions and expectations of the quality of Madrasah services. This phenomenological research uses a qualitative descriptive approach. To meet the needs of this study, researchers collected data by using observation, interview, and documentation techniques. The informants in this study included the head of the madrasa, integrated service staff, students, alums, and the madrasah committee. The results of the study indicate that there is urgency in implementing excellent services in madrasas, perceptions of community satisfaction with madrasa services, and the suitability of community expectations with the implementation of madrasa services. This study implies the importance of service in madrasa development activities that focus on customer satisfaction to survive and win the competition amid competition between educational institutions.